An Underreported Consequence of Obesity in Pregnancy: Patient-Prosthesis Mismatch. (8th July 2012) - Hartman, William R.; Arendt, Katherine W.; Rehfeldt, Kent H.
Abstract : As the rate of obesity increases in childbearing-aged women, so too will the complications of obesity in pregnancy. An uncommon and likely underreported complication occurs in obese women who have received prepregnancy cardiac valve replacement with a prosthesis that is inadequately sized for body habitus, a condition referred to as patient-prosthesis mismatch (PPM). The physiologic changes of pregnancy as well as the increased weight gain combine to exacerbate PPM. We report a case of PPM that necessitated prosthesis replacement at 16-week gestation. As the incidence of this clinical scenario increases, it is important to understand the implications of prosthesis sizing, as well as the repercussions of having cardiopulmonary surgery to correct the undersized valve prosthesis while pregnant.